A novel integrated approach on growing supply chain for multi-species poultries with carbon emission and preservation technology. (14th July 2022) - Tharani, S.; Uthayakumar, R.
This study comes up with a two echelon growing supply chain consisting of a primary poulterer and a secondary poulterer for multi-species poultries. We derive the mathematical growing inventory model with preservative technique, quantity discount and carbon emission. We classify the emission into two types, namely the direct and indirect emissions. We incorporate the quantity discount as a function of secondary poulterer's order quantity and it is inscribed to be all-unit-discount format. The objective is to maximise the profit function of both the poulterer individually and also integrated approach. Numerical illustrations and sensitivity are carried out to show the application of the proposed model. In this study, a genetic algorithm (GA) tool has been developed to find the expected maximum profit cost of the proposed inventory model. Also we compare the results of each poulterer individually with the integrated approach of two poulterers.